I IMPLEMENTASI METODE BAYES DALAM EVALUASI KEPUASAN MAHASISWA TERHADAP LAYANAN UNIVERSITAS - Dewi Suranti; Yupianti Yupianti; Venny Novita Sari (SINTECH (Science and Information Technology) Journal, 2021)
Student satisfaction towards services is a priority for each tertiary institution to improve the quality that is demanded by students. To improve the quality of education, universities must provide services provided to students. Dehasen University (Unified) Bengkulu promised to improve the quality standards of education and continue to improve and improve dissatisfaction in meeting student expectations. This is done to improve the quality standards of education and meet student expectations related to services that are the rights of students. By understanding the level of satisfaction of students, universities can improve performance in carrying out their duties and take responsibility for the quality of education, thus increasing the quality of services that can be improved. This study uses Bayes study, which is a classification method using probability and statistical methods based on the Bayes theorem. The aim is to implement Bayes to support student satisfaction with universities that support the following fields: Student Affairs, Library, Academic and Student Administration Bureau (BAAK), Facilities and infrastructure and finance. The results of this method produce Administrative and Academic Bureau services and financial services obtain Very Good satisfaction levels with a total service value of 12,183 with an excellent threshold value of 12,042 and a total service value of 9,413 with an excellent threshold value of 9,375. And the level of student satisfaction with the level of service is good, because the total value of results is 49,769 while the threshold is very good is 50,001 this means the total results below the threshold value is very good.